2020
DOI: 10.31538/nzh.v3i1.476
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Pendidikan Islam Di Thailand Pada Abad 19-20

Abstract: Thailand has two different parts of the region ranging from ethnics, culture, national and religion. However, due to religious differences, the trade route, which was a more profitable trading route in Southern Thailand, inhabited by Malay Patani, made the Siamese Kingdom want the area. The desires of the Siamese Kingdom were successful. So Patani Malay became part of the Thai Kingdom and its government system followed the policies adopted by the Thais, including in terms of Islamic education in Patani. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The kingdom experienced a victory system because the region was a trade route for European countries. The Pattani Kingdom lived in the south of the Kingdom of Siam (Aslan et al, 2020). The Pattani or Langkasuka kingdom emerged from the Malacca Malays who left the district during political turmoil in their own country under the rule of the Sriwijaya Kingdom (Pramudita, Fasisaka, & Kawatri Resen, 2015).…”
Section: History Of Thailandmentioning
confidence: 99%
See 1 more Smart Citation
“…The kingdom experienced a victory system because the region was a trade route for European countries. The Pattani Kingdom lived in the south of the Kingdom of Siam (Aslan et al, 2020). The Pattani or Langkasuka kingdom emerged from the Malacca Malays who left the district during political turmoil in their own country under the rule of the Sriwijaya Kingdom (Pramudita, Fasisaka, & Kawatri Resen, 2015).…”
Section: History Of Thailandmentioning
confidence: 99%
“…Based on research conducted by Niksah, it was found that the education policy carried out refers to the goal so that all components are directed to achieve that goal (Uma, 2020). As a conflict country, Aslan et al (2020) explained that Thailand has the intelligence of its political strategy and management system can make policy changes both socially, culturally, economically, politically, and educationally. Thailand supports education policy through the implementation of Thai government guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Identity politics innovators were not very well known during the New Order era about thinking (none of them were well known), which implies nothing unique compared to the Islamic figures currently being considered. The three typologies of Indonesian Islamic innovation above are everyday Islam, civilizational Islam, and authoritative Islam (Rouf, 2016;Suhardi et al, 2020;Aslan, 2018;Aslan et al, 2020;Aslan & Hifza, 2019). The core of every thought is about the development of objective innovation in Islam and the progress of Islam, especially on the issue of secularization in Islam, especially in the modernization of Islamic civilization.…”
Section: Current Politics and Identical Politicsmentioning
confidence: 99%
“…Education is one of the institutional sectors that is a concern of MA Daarul Uluum in their role to promote peace in Thailand. Since the implementation of the culture assimilation policy in southern Thailand also effects the identity uniformity in the education which violates multiculturalism values as their basic human needs that indirectly discriminates the Malay Moslem people and prompts conflict to occur (Aslan et al, 2020). In order to address those issues, MA Daarul Uluum sees the exchange program as capable of promoting peace and fulfilling human rights for all elements of society, with no discrimination towards a specific identity group, as a form of the goal to implement human rights education.…”
Section: Structural Transformationmentioning
confidence: 99%